Development of a Student Worksheet (LKPD) Integrated with the Qur'an and Hadith on the Digestive System Topic - Siti Nurhayati; Elsa Ofiarni; Tegi Tegi; Ummi Hiras Habisukan; Weni Lestari; Dur Brutu; Muhammad Sirajudin Fikri (MO.RI Publishing, 2026)
This study aims to develop a Student Worksheet (LKPD) integrated with Qur'anic verses and Hadith on the digestive system topic for senior high school students, as well as to determine its validity and practicality. The development model used was ADDIE, although the study was limited to the Analysis and Design stages. The instruments consisted of expert validation sheets (material, media, language, and Islamic studies experts) and practicality questionnaires for students and biology teachers. The validation results indicated that the LKPD was categorized as very valid, with the following scores: Islamic studies expert 94.66%, material expert 93.33%, media expert 97.33%, and language expert 97.33%. The practicality test results showed that the LKPD was rated very practical by students with a score of 89% and by biology teachers with a score of 90.66%. Accordingly, the Qur'an- and Hadith-integrated LKPD is considered feasible and suitable for use as a learning resource for the digestive system topic.